Homogenita repolarizace u patientů po akutním infarktu myokardu hodnocená z dlouhodobých 12svodových elektrokardiografických záznamů - Novotný, T; Dohnalová, I; Sisáková, M; Poloczek, M; Hnátková, K; Toman, O; Dostálová, L; Manousková, L; Floriánová, A; Kala, P; Spinar, J; Malik, M (Vnitrni lekarstvi, 2008)
BACKGROUND: Abnormal heterogeneity of myocardial electrophysiologic processes increases the risk of malignant arrhythmias. The aim of the studywas to assess changes ofrepolarization homogeneity in patients after acute myocardial infarction (MI) using morphological parameters obtained from long-term 12-lead electrocardiographic recordings. METHODS: In the group of 200 patients (45 females, 155 males) a long-term (10 minutes supine) 12-lead electrocardiographic recording (SEER MC, GE Medical) was performed 48-72 hours after acute myocardial infarction. The following parameters were calculated using experimental software: total cosine R to T (TCRT) and Twave residuum (TWR). The results were correlated with Q wave evolution and left ventricular ejection fraction (LVEF). RESULTS: Distinguishing the MI type (Q vs nonQ) the following values were obtained: TCRT: 0.17 +/- 0.61 vs 0.16 +/- 0.49, p = 0.52, absolute TWR: 21,200 +/- 21,700 vs 25,700 +/- 29,300, p = 0.3, relative TWR: 0.0012 +/- 0.0017 vs 0.0017 +/- 0.0026, p = 0.28. Stratification according to LVEF (< or = 40% vs > 40%) led to: TCRT: -0.03 +/- 0.66 vs 0.25 +/- 0.54, p = 0.01, absolute TWR: 29,700 +/- 32,400 vs 21,300 +/- 21,500, p = 0.14, relative TWR: 0.0021 +/- 0.0047 vs 0.0013 +/- 0.0021, p = 0.48. CONCLUSION: TCRT is a robust measurement of the spatial angle between the QRS complex and T wave loops which is related to LVEF. The results concerning TWR might indicate that this parameter is independent of LVEF, which needs to be confirmed in further analyses in a larger population.
Keywords: tepový objem; Electrophysiologic Techniques, Cardiac; Humans; Stroke Volume; funkce levé komory srdeční; lidé středního věku; Female; Aged; Electrocardiography, Ambulatory; senioři; lidé; infarkt myokardu; elektrofyziologické techniky kardiologické; ženské pohlaví; Male; Middle Aged; Myocardial Infarction; elektrokardiografie ambulantní; mužské pohlaví; Ventricular Function, Left